The importance of social work roles in disaster risk management in Zimbabwe - Machimbidza, Dickson; Nyahunda, Louis; Makhubele, Jabulani C. (Technium Social Sciences Journal, 2022)
This study was aimed at exploring the efficacy of social work roles in disaster risk management in Zimbabwe in the face of climatic changes. It was carried out in Binga district, Matebeleland-North province using the qualitative methodology and a case study design. The study sample was comprised of 8 practicing social workers. Snowballing and purposive sampling techniques were used to select these participants. Data were collected through in-depth interviews using an interview guide. Thematic content analysis was employed to analyze the collected data. It was found that social workers play essential roles before, during and after disasters. On disaster preparedness, it was established that social workers assume roles of educators, community workers and disaster planners. Moreover, it was found that they play the roles of case managers, administrators of social protection and counselors during the disaster response phase of disaster risk management. Subsequently they also act as advocates, development facilitators as well as monitoring and evaluation personnel in the disaster recovery phase. As per the findings, the study recommends that social workers be recognized as essential in disaster risk management at both policy and practice level. Further, there is need to enhance social work training education for flexibility and contextual application of social work knowledge in the field of disaster risk management for quality realization of green social work in Zimbabwe.